"SPORTS ARE FUN": A Guide for the Discussion of Sport-Related Films - Robert P. Olympia MD; Christy Lucas BS; Vignesh Doraiswamy MD; Cristina Funghi MD; Hannah M. Wakefield MD, MPH; Bryan H. Wakefield PhD; Jodi Brady MD (SAGE Publishing, 2019)
Sport participation is an important part of the development of children and adolescents in the United States. Due to the popularity of sport-related films, coaches, athletic trainers, and parents have used these films to both educate and motivate pediatric athletes. The objective of this study was to develop a discussion guide template based on common positive and negative themes depicted in sport-related films, and demonstrate the application of this discussion guide template to a select number of sport-related films released from 2014 to 2018. A discussion guide template ("SPORTS ARE FUN") was developed by the co-investigators, reflecting common themes of " S portsmanship, P articipation for All, O bstacles, R elationships, T eamwork, S etting Realistic Goals, A cademics, R esponsibility, E xercise/Nutrition/Rest/Drugs/Performance Enhancing Drugs, F un, U nrelenting Spirit, and " N o Pain, No Gain." The authors hope that pediatric health care providers, athletic coaches/staff, and parents can utilize this discussion guide template in the education and development of children and adolescents who participate in sports.